Synthesis and Crystal Structure of N,N´-1,2-Phenylenebis-(salicylideneiminato)Copper(II) monohydrate - Zhang, Shu-Sheng; Yang, Bo; Wang, Yan-Fang; Li, Xue-Mei; Jiao, Kui (Asian Journal of Chemistry, 2016)
In the title compound (C20H14N2O2Cu).H2O, the space group is R-3 with a = b = 31.676(7), c = 9.040(6) Å, a = b = 90, g = 120º, belonging to none of the seven crystal systems. The crystal used to collect the present data was twinned. The complex is formed with cis-N,N´-1,2-phenylene-bis(salicylideneiminato) ligand and shows nearly planar geometry. The Cu atom is coordinated by the O and N atoms of the ligand and has a distorted square-planar geometry. The water molecule is bonded to both acceptor O atoms, viz., O1W-H1W1 … O1 and O1W-H2W1 … O2 intermolecular interactions. The packing is stabilized by the n-n interactions.